Forensic Examination Timelines in Sexual Violence Cases: A Comparative Legal Study of Evidentiary Effectiveness - Handar Subhandi Bakhtiar; Handina Sulastrina Bakhtiar; Ahmad Yusup (NAJAHA, 2026)
Forensic examinations in sexual violence cases are inherently time-sensitive and play a decisive role in ensuring evidentiary effectiveness and the protection of victims’ rights. Delays in forensic examinations significantly reduce the probative value of evidence, thereby weakening the burden of proof and undermining legal certainty within criminal proceedings. In Indonesia, the absence of explicitly regulated forensic examination time limits under the Criminal Procedure Code (KUHAP) and Law No. 12 of 2022 on Sexual Violence Crimes (UU TPKS) reveals a normative gap that diminishes the effectiveness of evidence and compromises victim protection. This issue is directly relevant to the achievement of the Sustainable Development Goals (SDGs), particularly SDG 5 (Gender Equality) and SDG 16 (Peace, Justice, and Strong Institutions), as it affects access to justice and institutional accountability in handling sexual violence. This study aims to analyse the regulatory framework governing forensic examinations in sexual violence cases in Indonesia, assess the normative urgency of establishing forensic time limits, and conduct a comparative legal analysis between Indonesia and selected jurisdictions, namely the United Kingdom, the United States, Australia, and South Korea. This study employs normative (doctrinal) legal research, using a statutory approach and a comparative law approach. The analysis is based on primary legal materials, including KUHAP, UU TPKS, health regulations, and forensic standard operating procedures, supported by secondary legal doctrine and forensic guidelines. The findings indicate that the lack of binding forensic timelines in Indonesia contributes to delayed evidence collection and excessive reliance on victim testimony. In contrast, comparison countries, although similarly lacking explicit statutory limits, rely on institutional and healthcare guidelines that establish forensic examination timeframes ranging from 24 hours and 72 hours to a maximum of seven days, thereby enhancing evidentiary reliability. This study contributes original normative insights by linking forensic time regulation with legal certainty, evidentiary theory, and victim-centred justice, and proposes policy-oriented recommendations for strengthening Indonesia’s criminal justice framework.